Barriers to modern contraceptive utilization in Ethiopia - Tigist Shumet; Nigatu Regassa Geda; Jemal Ali Hassan (BMC, 2024)
Abstract Background Contraception is a critical service for women to control their reproductive health, allowing them to determine the number and spacing of their children prevent unintended pregnancies, reduce the risk of morbidity and mortality from associated with childbirth, and reduce the likelihood of abortions. Despite its benefits, the utilization of modern contraceptive methods remains low in certain regions of Ethiopia, Particularly in Afar and Somali, which are also experiencing high fertility rates. However, there is a substantial gap in understanding the sociocultural barriers that hinder the adoption of modern contraception in these regions. This study aims to explore these barriers to contraceptive use among women of reproductive age in Afar and Somali regions, providing qualitative insights that are essential for designing effective strategies to improve contraceptive service utilization. Methods Asequential mixed method approach was employed, including scoping review and qualitative interviews. Scoping review focused on qualitative or mixed-methods studies conducted in Ethiopia and published between 2013 and 2023 in English, Selecting 14 articles Additionally, qualitative data were collected from Afar and Somali regions through In-depth interviews with women aged 15-49 who are married or in consensual union, and key informant interviews with health extension workers and contraception providers at health center. A total of 20 in-depth interviews and 07 key informants were conducted. Thematic analysis was used to analyze the data. Result The integrated findings from the scoping review and qualitative study reveal various barriers and determinants influencing contraceptive use among women in Ethiopia. Barriers includes religious or cultural beliefs, myths and misconceptions, fear of side effects, lack of knowledge and misinformation, negative attitude towards contraceptives, partner opposition, socio-cultural factors, fear of being judged by family and friends, and lack of communication between husband and wife, husband altitude, distance from health facility, availability of service and different contraceptive choice, separate room for family planning services, and cost of contraceptive method and transportation. The scoping review corroborates these findings, emphasizing on the role of socio-demographic, economic, cultural, religious, health service, and knowledge-related factors. Higher education, urban residence, higher income, mass media exposure, spousal communication, family size, and access to quality health services were associated with increased utilization, while lack of awareness, misconceptions, myths, side effects, fear of infertility, partner opposition, social stigma, and cultural norms decreased utilization. Conclusion The study recommended promoting contraceptive use, challenging socio-cultural norms through Social Behavioural Communication and Counselling (SBCC), engaging partners and community members, and improving the quality of care.